Time-in-a-Bottle (TIAB): A Longitudinal, Correlational Study of Patterns, Potential Predictors, and Outcomes of Immunosuppressive Medication Adherence in Adult Kidney Transplant Recipients - Russell, Cynthia L. (2013)
This study examined patterns, potential predictors, and outcomes of immunosuppressive medication adherence in a convenience sample of 121 kidney transplant recipients aged 21 years or older from three kidney transplant centers using a theory-based, descriptive, correlational, longitudinal design. Electronic monitoring was conducted for 12 months using the Medication Event Monitoring System. Participants were persistent in taking their immunosuppressive medications, but execution, which includes both taking and timing, was poor. Older age was the only demographic variable associated with medication adherence (r = 0.25; p = 0.005). Of the potential predictors examined, only medication self-efficacy was associated with medication non-adherence, explaining about 9% of the variance (r = 0.31, p = 0.0006). The few poor outcomes that occurred were not significantly associated with medication non-adherence, although the small number of poor outcomes may have limited our ability to detect a link. Future research should test fully powered, theory-based, experimental interventions that include a medication self-efficacy component.